Human herpesvirus 6, 7, and 8 in solid organ transplantation: Guidelines from the American Society of Transplantation Infectious Diseases Community of Practice. Issue 9 (4th April 2019) - Pellett Madan, Rebecca; Hand, Jonathan; ,
Abstract: These updated guidelines from the Infectious Diseases Community of Practice of the American Society of Transplantation review the diagnosis, prevention, and management of HHV‐6A, HHV‐6B, HHV‐7, and HHV‐8 in the pre‐ and post‐transplant period. The majority of HHV‐6 (A and B) and HHV‐7 infections in transplant recipients are asymptomatic; symptomatic disease is reported infrequently across organs. Routine screening for HHV‐6 and 7 DNAemia is not recommended in asymptomatic patients, nor is prophylaxis or preemptive therapy. Detection of viral nucleic acid by quantitative PCR in blood or CSF is the preferred method for diagnosis of HHV‐6 and HHV‐7 infection. The possibility of chromosomally integrated HHV‐6 DNA should be considered in individuals with persistently high viral loads. Antiviral therapy should be initiated for HHV‐6 encephalitis and should be considered for other manifestations of disease. HHV‐8 causes Kaposi's sarcoma, primary effusion lymphoma, and multicentric Castleman disease and is also associated with hemophagocytic syndrome and bone marrow failure. HHV‐8 screening and monitoring may be indicated to prevent disease. Treatment of HHV‐8 related disease centers on reduction of immunosuppression and conversion to sirolimus, while chemotherapy may be needed for unresponsive disease. The role of antiviral therapy for HHV‐8 infection has not yet been defined.